2015
DOI: 10.1108/ijchm-06-2014-0275
|View full text |Cite
|
Sign up to set email alerts
|

“LuXurY” hotel loyalty – a comparison of Chinese Gen X and Y tourists to Macau

Abstract: Purpose; – This study aims to investigate generational disparities of Chinese Generation (Gen) X and Y tourists by examining their loyalty determinants in a luxury hotel setting. Design/methodology/approach – A survey of five-star hotel guests in Macau yielded 285 complete responses. Structural equation modeling was used to test the quality-loyalty framework through the mediating roles of perceived value and satisfaction, with a multi-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 62 publications
(81 reference statements)
4
36
0
4
Order By: Relevance
“…In a similar study, Jin, Lin and Hung (2014) found that Post-80s' expectations of outbound group tours were shaped by cultural values developed in Chinese Post-80s' pre-adulthood which influenced the perceived importance attached to service attributes. A closer examination of the relevant research concerning Chinese Post-80s tourists reveal that current studies tend to: 1) focus primarily Chinese Post-80s' tourist experience within mainland China (Wen, Lehto, Sydnor, & Tang, 2014) or nearby regions (Ong & du Cros, 2012); 2) study Chinese international student groups (Gardiner & Kwek, 2017;King & Gardiner, 2015); 3) focus on Chinese independent tourists generally who might not be necessarily be representative of Chinese Post-80s (Wu & Pearce, 2014); and 4) use a quantitative approach and adopt existing Western constructs (T. Jin et al, 2014;Yang & Lau, 2015). While many of these studies offer a descriptive analysis of a particular aspect of this generation, they tend to lack depth, partly due to a failure to demonstrate an understanding of the formative experiences which have shaped the attitudes and values that contribute to their current tourist experience (Lian, 2014 (Buckley et al, 2014).…”
Section: Conceptual Framework Of Chinese Post-80smentioning
confidence: 99%
See 2 more Smart Citations
“…In a similar study, Jin, Lin and Hung (2014) found that Post-80s' expectations of outbound group tours were shaped by cultural values developed in Chinese Post-80s' pre-adulthood which influenced the perceived importance attached to service attributes. A closer examination of the relevant research concerning Chinese Post-80s tourists reveal that current studies tend to: 1) focus primarily Chinese Post-80s' tourist experience within mainland China (Wen, Lehto, Sydnor, & Tang, 2014) or nearby regions (Ong & du Cros, 2012); 2) study Chinese international student groups (Gardiner & Kwek, 2017;King & Gardiner, 2015); 3) focus on Chinese independent tourists generally who might not be necessarily be representative of Chinese Post-80s (Wu & Pearce, 2014); and 4) use a quantitative approach and adopt existing Western constructs (T. Jin et al, 2014;Yang & Lau, 2015). While many of these studies offer a descriptive analysis of a particular aspect of this generation, they tend to lack depth, partly due to a failure to demonstrate an understanding of the formative experiences which have shaped the attitudes and values that contribute to their current tourist experience (Lian, 2014 (Buckley et al, 2014).…”
Section: Conceptual Framework Of Chinese Post-80smentioning
confidence: 99%
“…Chinese Post-80s tourists demonstrate significant differences from other tourist groups including the Japanese waves in the late 1980s and early 1990s (Breakey, Ding, & Lee, 2008), previous generations of Chinese tourists (Prayag, Disegna, Cohen, & Yan, 2015;Yang & Lau, 2015) and their Western counterparts (Gardiner & Kwek, 2017;King & Gardiner, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even for the same service or product, two individuals who share very similar socioeconomic status may make different decisions due to their experiences such as knowledge, taste, consumption frequency, and involvement (Martinez et al, 2006). In a recent study, Yang and Lau (2015) also confirm that different generations (X vs. Y) may possess different attitudes toward the loyalty in the hotel industry. For instance, Generation X is value-centered in building loyalty; Generation Y focuses both on value and upscale quality features.…”
Section: Passenger Heterogeneitymentioning
confidence: 52%
“…In terms of age, about 22.8% of respondents were above 36, 48.9% between 26 and 35, and 24.3% between 18 and 25. Half of the respondents were born in the 1980s, which is a distinctive generation in China with unique characteristics (Yang & Lau, 2015). This is also the emerging source market for Chinese outbound tourism.…”
Section: Instrumentmentioning
confidence: 99%